OSCON Open Source Software Superstream Series : Infrastructure - McCullough, Brianna; McCullough, Brianna; Patterson, Nicole; Lewis, Bridget; Grygleski, Mary; Jansen, Grace; Le-Nguyen, Tiffany; Ginn, Robin; Wang, Rosemary (O'Reilly Media, Inc., 2020)
This three-part series of half-day online events gives attendees an overarching perspective of software development from which to make decisions that strengthen and grow companies and industries, a deep knowledge of key open source technologies to make it happen, and a community in which both they and their companies can thrive. In part 2, we wanted to explore infrastructure, containers, continuous delivery, monitoring, chaos engineering, and SRE. Infrastructure today is wildly more complicated--and the wall between software development and deployment is dust. We'll shed light on new paradigms and a slew of tooling options for observability, testing, and reactive programming. This event is sponsored by IBM and features spotlights on the Caribbean Girls Hack.